Need help with all please??!!!!
Need help with all please??!!!! - 1

Answers

Answer 1
Answer: 9.V = (√(3))/(2)a^(2)h
   V = (√(3))/(2)(4)^(2)(8)
   V = (√(3))/(2)(16)(8)
   V = (√(3))/(2)(128)
   V = (128√(3))/(2)
   V = 64√(3)\ cm^(3)
The answer is D.

10. V = ¹/₃πr²h
      V = ¹/₃(3.14)(6)²(10)
      V = ¹/₃(3.14)(36)(10)
      V = ¹/₃(3.14)(360)
      V = ¹/₃(1130.4)
      V = 376.8 cm³
The answer is C.

11. V = ¹/₃πr²h
      V = ¹/₃(3.14)(6)²(10)
      V = ¹/₃(3.14)(36)(10)
      V = ¹/₃(3.14)(360)
      V = ¹/₃(1130.4)
      V = 376.8 cm³
The answer is C.

12. V = 1
¹/₃πr³
      V = 1¹/₃(3.14)(3)³
      V = 1¹/₃(3.14)(27)
      V = 1¹/₃(84.78)
      V = 113.04 cm³
The answer is C.

13. V = 1¹/₃πr³
      V = 1¹/₃(3.14)(12)³
      V = 1¹/₃(3.14)(1728)
      V = 1¹/₃(5425.92)
      V = 7234.56 cm³
The answer is A.

14.        S = 4πr²
        324π = 4(3.14)(r)²
324(3.14) = 4(3.14r²)
   1017.36 = 12.56r²
     12.56      12.56
            81 = r²
              9 = r

V = 1¹/₃πr³
V = 1¹/₃(3.14)(9)³
V = 1¹/₃(3.14)(729)
V = 1¹/₃(2289.06)
V = 3052.08
The answer is D.

15. The answer is A.
16. The answer is A.
17. The answer is B.
18. The answer is C.
Answer 2
Answer: 13. c
14. d
15. b
Sorry if I am not correct I'm only in 6th grade

Related Questions

7x-5y=20 in slope intercept form
Start at 200.Create a pattern that multiplies each number by 2.Stop when you have 5 numbers.
2x + 3y = 34x + 6y = 10One Solution Infinitely Many SolutionsNo Solutions
In one day, Annie traveled 5 times the sum of hours Brian traveled 2. Together they traveled 20 hours. Find the number of hours each person travels
Can someone please help me with this? As a reward, you will get a brainly for the right answer!

Write an equation to represent eachrelationship. SOLVE THE EQUATION.
5 more than six times a number is the
same as that number decreased by ten.

Answers

n6+5=n-10
n6=n-15
n5=-15
n=-3
hope this helps:)

If the vertices of triangle bcd are b(-3,3), c(3,5), and d(-1,0), what is the perimeter

Answers

distance formlula
D=\sqrt{(x2-x1)^(2)+(y2-y1)^(2)}

when you want to find the distance between points (x1,y1) and (x2,y2)


we nee
distace from
b to c
c to d
d to b


b to c is (-3,3) to (3,5)
D=\sqrt{(3-(-3))^(2)+(5-3)^(2)}=2√10

c to d is (3,5) to (-1,0)
D=\sqrt{(-1-3)^(2)+(0-5)^(2)}=√41

d to b is (-1,0) to (-3,3)
D=\sqrt{(-3-(-1))^(2)+(3-0)^(2)}=√13

add

b to c+c to d+d to b=2√10+√41+√13

perimiter=2√10+√41+√13 units





$0.60 bottle of iced tea marked up to $1.35

Answers

complete question:

$0.60 bottle of iced tea marked up to $1.35. Find the percentage markup.

Answer:

percentage markup = 125%

Step-by-step explanation:

$0.60 bottle of iced tea marked up to $1.35. The marked up percentage can be calculated as follows:

1.35/0.60 = p/100

2.25 = p/100

2.25 = p/100

multiply both sides by 100

2.25 × 100 = p

225%

Therefore the mark up is 225 - 100 = 125%

percentage markup = 125%

The answer is 0.81 since you have to (x) 0.60x 1.35=0.81 Than you divide 0.81÷0.60

Use the Laplace transform to solve the given initial value problem. y' + 6y = e^4t ; y(0)=2 ...?

Answers

Performing laplace transform of the equation.

sY(s) - y(0) + 6Y(s) = 1/(s-4)
(s+6)Y(s) - 2 = 1/(s-4)
Y(s) = 2/(s+6) + 1/(s-4)(s+6), by partial fraction decomposition
Y(s) = 2/(s+6) + 1/10 * (1/(s-4) + 1/(s+6))
Y(s) = 0.1/(s-4) + 2.1/(s+6)

Performing inverse laplace transform,
y(t) = 0.1e^4t + 2.1e^(-6t)


I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!

Final answer:

The Laplace transform method is applied to solve the differential equation y' + 6y = e^4t with the initial condition y(0)=2. After transforming, simplifying, and solving for Y(s), we use inverse Laplace transform to find the solution y(t) in the time domain.

Explanation:

Laplace transform is a powerful tool in the field of mathematics used for solving differential equations. To solve the given initial value problem y' + 6y = e^4t ; y(0)=2, we can start by taking the Laplace transform of both sides of the equation.

The Laplace transform of y' is sY(s) - y(0) and the Laplace transform of y is Y(s). Therefore, the Laplace transform of y' + 6y gives sY(s) - y(0) + 6Y(s). Given that y(0)=2, this simplifies to sY(s) + 6Y(s) - 2.

On the right-hand side, the Laplace transform of e^4t is 1/(s-4). Thus, we have the equation sY(s) + 6Y(s) - 2 = 1/(s-4).

By solving for Y(s), we can find the inverse Laplace transform to get the solution y(t) in the time domain.

Learn more about Laplace Transform here:

brainly.com/question/31481915

#SPJ6

Given that f(x) = x^2 + 6x – 2, g(x) = x – 7, and h(x) = x + 4find each function. (f + g)(x)

Answers

Answer:

  (f+g)(x) = x^2 + 7x -9

Step-by-step explanation:

(f + g)(x) = f(x) + g(x)

  = (x^2 + 6x – 2) + (x – 7)

  = x^2 + 7x -9

Edwards aquifer was 700.7 feet. Rounded to the nearest foot how would this depth be expressed?

Answers


The next larger foot is  701 .
The next smaller foot is  700.
700.7  is closer to  701  than it is to  700 .
So  700  is the nearest whole foot.